KAJIAN YURIDIS PASAL 27 AYAT (1) UNDANG - UNDANG NO 11 TAHUN 2008 TENTANG TINDAK PIDANA SIBER KESUSILAAN - Evi Retno Wulan (Fakultas Hukum Universitas Narotama, 2020)
The types of cyber crime are regulated in article 27 to article 37 of Law No. 11/2008 of Juncto Law No. 19/2016. The author is interested in analyzing the formulation of article 27 paragraph (1) regarding criminal acts of decency with his explanation in Law No. 11/2008 Juncto Law No. 19/2016, because the elements of a moral act in the formulation of article 27 paragraph (1) are unclear and can cause different perceptions. Regulations regarding the formulation of criminal acts in the law, in this case specifically the formulation of criminal acts in Law No. 11/2008 in conjunction with Law No. 19/2016 must be clear, easy to understand, and carried out fairly. Unclear criminal acts formulations can potentially lead to legal uncertainty. The author tries to reveal the unclear formulation of the provisions of article 27 paragraph (1) of Law No. 11/2008 which regulates the provisions on criminal acts of decency. This has become an urgent need and cannot be delayed, because it involves the issue of legal certainty. Key words: cyber crime, decency, legal certainty, article formulation, information technology